Germline-Restricted Chromosome (GRC) in Female and Male Meiosis of the Great Tit (Parus major, Linnaeus, 1758) - Torgasheva, Anna; Malinovskaya, Lyubov; Zadesenets, Kira; Shnaider, Elena; Rubtsov, Nikolai; Borodin, Pavel (Frontiers in Genetics, 2021)
All songbirds studied so far have a germline-restricted chromosome (GRC), which is present in the germ cells and absent in the somatic cells. It shows a wide variation in size, morphology, and genetic content between the songbird species. In this paper, we analyzed GRC behavior in female and male meiosis of the great tit, using immunolocalization of meiotic proteins and FISH with GRC-derived DNA probes. We found that, despite dozens of million years of independent evolution, the great tit GRC displays a striking similarity with the GRCs of two species of martins and two species of estrildid finches examined earlier. It was usually present in two copies in females forming recombining bivalent and in one copy in males forming a condensed heterochromatic body with dotted-like axial elements of the synaptonemal complex. We observed mosaicism for the GRC copy number in the female and male great tit. This indicates that one of the GRC copies might be passively lost during premeiotic germ cell divisions. After the meiotic prophase, the GRC was ejected from most male germ cells. The reverse and interspecies FISH with GRC-specific microdissected DNA probes indicates that GRCs of the great tit, pale martin, and zebra finch differ substantially in their genetic content despite similarities in the meiotic behavior.